Análise e seleção de mercado para internacionalização da Vinícola Salvati & Sirena - Salvati, Teilor (My University, 2023)
In the context of a globalized economy, the pursuit of internationalization stands as a pivotal strategy for enterprises seeking growth and enduring viability, including within the viticultural sector. This case study, centered on Vinícola Salvati & Sirena, located in the wine-producing region of Bento Gonçalves, sets out to chart the international wine market and pinpoint prospective export destinations. Through a nuanced comparative market analysis, leveraging PESTEL analysis and a rigorous market selection framework, the United Kingdom has emerged as the most auspicious market. This country is distinguished by a discerning consumer base whose preferences resonate with the company's offerings and a sociocultural context that presents an accommodating backdrop for market incursion. The insights gleaned from this study are determinant for Vinícola Salvati & Sirena, signaling viable markets and formulating blueprints for international triumph. The findings present promising prospects for the company, and also contribute to the literature on international wine trade, underscoring the importance of a multifaceted market analysis in strategic decision-making. [resumo fornecido pelo autor]
Em um ambiente econômico globalizado, a internacionalização surge como uma estratégia oportuna para empresas que visam crescimento e sustentabilidade, inclusive para o setor vitivinícola. Este estudo de caso da Vinícola Salvati & Sirena, localizada na região vinícola de Bento Gonçalves, tem como objetivo central mapear o panorama internacional de vinhos e identificar mercados exportadores potenciais. Através de uma investigação mercadológica comparativa, utilizando-se da Análise PESTEL e a aplicação de critérios de seleção de mercado, o Reino Unido revelou-se como o destino mais promissor, marcado por um consumo sofisticado e alinhado com o portfólio da empresa, além de um contexto sociocultural favorável. As descobertas presentes neste trabalho são estratégicas para a Vinícola Salvati & Sirena, indicando mercados potenciais e esboçando estratégias para o sucesso internacional. Os resultados oferecem perspectivas promissoras para a empresa, bem como se soma à literatura sobre o comércio internacional de vinhos, destacando a importância de uma análise de mercado multifacetada na tomada de decisões estratégicas. [resumo fornecido pelo autor]
Keywords: Comércio internacional; Vinícolas